Once bitten, twice shy?: Lessons learned from an experiment to liberalize price regulations for dental care - Trescher, Anna-Lena; Listl, Stefan; Galiën, Onno van der; Gabel, Frank; Kalmus, Olivier (The European journal of health economics, 2020)
In 2012, The Netherlands established the so-called “free market experiment”, which allowed providers of dental care to set the prices for their dental services themselves. The introduction of market mechanisms is intended to improve the quality of care and to contribute to cost containment, but increasing health expenditures for citizens have been observed in this context. Using large-volume health insurance claims data and exploiting the 2012 experiment in Dutch dental care, we identified the effects of a liberalization of service prices. Using pooled regression with individual fixed effects, we analyzed changes in utilization patterns of prevention-oriented dental services in response to the experiment as well as the elasticities in demand in response to variations in out-of-pocket (OOP) prices. We found substantial increases in prices and patients’ OOP contributions for dental services following the liberalization with differences in increases between types of services. In response to the experiment, the proportion of treatment sessions containing preventive-oriented services decreased significantly by 3.4% among adults and by 5.3% for children and adolescents. Estimates of short-run price elasticities of demand for different services point towards differences in price sensitivity. One potential explanation for the observed variations in prices and utilization could be different extents of asymmetric information for first-stage and follow-on services. Price liberalization seems to have affected the composition of treatment sessions towards a decreasing use of preventive services, suggesting a shift in the reason for seeing a dental care provider from a regular-preventive perspective to a symptom-based restorative approach.